Transisi kepemimpinan pastoral menuju emeritasi dan dinamika family enterprise dalam Gereja-gereja Pentakostal di Indonesia - Mahendra, Yogi (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This research examines the transition of pastoral leadership towards emeritation in Indonesian Pentecostal churches that face the challenge of family-based leadership inheritance. The study aims to formulate an emeritation model based on the principle of Spirit-led pneumatocratic leadership. Using a constructive approach, the research developed an integrative model through analysis of theological literature, case studies, and church governance practices. Findings show that the practice of informal inheritance weakens accountability and the quality of spiritual ministry. The emeritation model offered includes six stages: theological affirmation, strategic planning, spiritual mentoring, the empowerment of contemporary competencies, honouring emeritus pastors, and periodic evaluation. The design of this model supports the regeneration of healthy and relevant leadership through a spiritual transformation process. Thus, Indonesian Pentecostal churches can strengthen leadership regeneration while maintaining a balance between spiritual authority and public accountability. Abstrak Penelitian ini mengkaji transisi kepemimpinan pastoral menuju emeritasi dalam Gereja-gereja Pentakostal Indonesia yang menghadapi tantangan pewarisan kepemimpinan berbasis keluarga. Tujuan penelitian adalah merumuskan model emeritasi berdasarkan prinsip kepemimpinan pneumatokratis yang dipimpin Roh Kudus. Menggunakan pendekatan konstruktif melalui analisis literatur teologis, studi kasus, dan praktik pemerintahan gereja, penelitian ini menyusun model integratif. Temuan menunjukkan praktik pewarisan informal melemahkan akuntabilitas dan kualitas pelayanan rohani. Model emeritasi yang ditawarkan mencakup enam tahap: peneguhan teologis, perencanaan strategis, mentoring spiritualitas, pemberdayaan kompetensi kontemporer, penghormatan pendeta emeritus, serta evaluasi berkala. Model ini dirancang sebagai proses transformasi rohani yang mendukung regenerasi kepemimpinan yang sehat dan relevan. Dengan demikian, Gereja-gereja Pentakostal Indonesia dapat memperkuat regenerasi kepemimpinan sambil menjaga keseimbangan antara otoritas rohani dan akuntabilitas publik.